Status Hukum Masyarakat Suku Bajo di Kelurahan Bajoe Kecamatan Tanete Riattang Timur Kabupaten Bone - Taheriah, Nuragifah; Salam, Safrin; Salam, Shinta Nurhidayati (Rechtsregel : Jurnal Ilmu Hukum, 2025)
Indonesia, as an archipelagic state, possesses the second-longest coastline in the world, with more than 70% of its population residing in coastal areas. Among these coastal communities, the Bajo people are renowned for their long-standing maritime culture and reputation as skilled seafarers. Social transformation has shifted much of the Bajo population from a nomadic life at sea to permanent settlements along the coast, including Kampung Bajo in Bajoe Village, Tanete Riattang Timur District, Bone Regency. This transition raises critical questions regarding the certainty of their legal status. This study examines the legal status of the Bajo community in Kampung Bajo, Bajoe Village, Tanete Riattang Timur District, Bone Regency. Employing a socio-legal research approach within the framework of empirical legal studies, the research utilizes both primary and secondary data, gathered through interviews with local government officials and community leaders, and complemented by literature review. The data were analyzed qualitatively. The findings indicate that within the classification of three types of coastal communities, the Bajo in Kampung Bajo fall into the category of Traditional Communities. Although they continue to uphold traditional values in settlement and fishing practices, their customary institutions no longer exist.